Low density lipoprotein receptor: Interaction with ligands and molecular chaperone proteins. - Chauhan, Vinita. (University of Ottawa (Canada), 2001)
The low density lipoprotein receptor (LDLr) is a complex multi-domain protein that is involved in the maintenance of cholesterol homeostasis. To study the kinetics of interaction of lipoproteins to the LDLr, we produced truncated forms of the LDLr that included the ligand-binding domain with and without the EGF homology domain. In the absence of the EGF precursor homology domain the receptor was secreted from Chinese hamster ovary (CHO-K1) cells as inactive, disulfide-linked multimers. In contrast, in the presence of the EGF precursor homology domain the receptor was secreted as a functional monomeric species. These observations led us to believe that inter-domain interactions may be involved in producing an active receptor. Since many mutations that cause familial hypercholesterolemia (FH) map to the EGF precursor homology domain, we expressed the EGF precursor homology domain as a separate polypeptide in order to determine if it could act in trans to assist in the proper folding of the ligand-binding domain. We propose a model, whereby an initial co-translational stabilization of the ligand-binding domain by chaperone proteins is followed by a post-translational interaction of the EGF repeats with the ligand-binding domain to yield a properly folded and functional receptor. Low density lipoproteins (LDL) are heterogeneous in terms of size, lipid composition and protein conformation. These factors influence the ability of LDL to bind to the LDLr. The binding of lipoproteins to the LDLr is also modulated by a number of other factors including ligand conformation, cell surface proteoglycans and steric hindrance. Surface plasmon resonance (SPR) was used to determine the affinity and kinetics of the LDL-LDLr interaction. This technology allows for interactions to be continuously monitored in real time and generates binding profiles from which rate constants can be derived. To minimize lattice effects and to exclude the participation of other cell surface components, a soluble N-terminal 692 amino acid LDLr fragment was stably produced in mammalian cells. The LDLr was expressed at 10 mug/ml and could be immuno-purified to homogeneity using the anti-LDLr monoclonal antibody, C7. The LDLr bound biotinylated LDL on a ligand blot and, when monitored by SPR, it could bind native but not acetylated LDL, which demonstrates its physiological specificity. The kinetics of binding fit a model in which a conformational change in the receptor and/or the ligand occurs following the initial binding that converts a low affinity complex to a high affinity complex with a slow dissociation rate. To determine the effect of LDL heterogeneity on the kinetics of binding, LDL from hypertriglyceridemic patients was tested. The small, dense and triglyceride-enriched particles bound the LDLr with similar conformational kinetics as native LDL.
Keywords: Chemistry, Biochemistry.